An Experimentalist Who Shunned Hypotheses? A Study of François Magendie’s Experimental Medicine - Chanwoong PARK (Uisahak)
The advent of experimental medicine in the early nineteenth century marked a crucial turning point in history of medicine. Historians unanimously recognize François Magendie (1783-1855), a physician and physiologist, as a pioneer of experimental medicine. Despite his significance, research on Magendie’s achievements and contributions remains limited. This scarcity stems from conflicting evaluations of Magendie's experimental medicine. On one hand, some claim that Magendie avoided hypotheses and simply accumulated individual facts. On the other hand, others argue that he implicitly used hypotheses. These differing views traces back to his disciple Claude Bernard (1813-1878), who believed it was impossible to conduct experiments without hypotheses. If Magendie was a pioneer of experimental medicine, then he must have had hypotheses as well. However, interpretations of his viewpoint on hypotheses vary. This paper aims to clarify this issue. By examining contemporary evaluations of physiology during Magendie’s time, the concept of collaborative research with chemist Antoine-Laurent Lavoisier (1743-1794), and the laboratory environments where these ideas were realized, this study finds new insights into Magendie’s approaches to experimental medicine. Magendie was extremely cautious in formulating his own hypotheses, but he often designed experiments based on the hypotheses of other physiologists. His criticism of Bichat exemplifies this tendency. The conclusions derived from this study are as follows: first, there is a need to reconsider the current historical understanding of Magendie's experimental medicine; second, the history of early nineteenth century medicine, particularly in the context of large-scale collaborative research, requires a different analytical approach than that applied to earlier periods.